Identifying Cultural Traits of the Historic Kampong Ayer of Brunei Darussalam using Biomimetic Analysis - Yong, Gabriel Yit Vui (International Journal of Environment, Architecture, and Societies, 2021)
Kampong Ayer is the cultural hearth of Brunei Darussalam. Once described as the Venice of the East, modernization has transformed this capital of the Brunei Sultanate into just another urban settlement, but located within the Sungai Brunei estuary. Its largely modern architecture and built environment has raised the question of whether it still holds any heritage value. This paper aims to provide an answer using the UNESCO World Heritage Site enlistment criteria as a guide. The study focusses on the relationship between people and environment (Criteria 5) to determine if they could be regarded as an outstanding example that is vulnerable to irreversible change. It employs a biomimetic approach to analysis as field surveys suggest the environment to be a prominent factor. The information used was gathered over the past decade through field work and dialogue with current and former residents. The study found a good degree of congruence between residents of Kampong Ayer and mangroves, the ‘genius of place’ in the Sg Brunei estuary. It also found processes and patterns typical of organismic, evolving systems. The study elucidated cultural traits that have survived through the evolution of Kampong Ayer over half a millennium. The paper also addresses sustainability issues using findings from biomimetic analysis.